Direct and indirect experiences with heterosexism: How slurs impact all students. Issue 2 (3rd April 2018) - Norris, Alyssa L.; McGuire, Jenifer K.; Stolz, Cheryl
ABSTRACT: Students targeted by homophobic discrimination are at risk for poor academic outcomes, yet few studies have examined how witnessing discrimination affects students. This study examined the impact of direct and indirect experiences of heterosexism on feelings of safety, belongingness, and connectedness among a sample of 1, 702 students at a public university in the Western United States. Sexual minority students were more likely to be a target of and witness to discrimination, and they reported significantly lower levels of safety and belongingness. Hierarchical multiple regression analyses revealed that witnessing discriminatory acts contributed significantly to lower levels of safety, belongingness, and connectedness among heterosexual students, even after accounting for personal experiences with discrimination. For sexual minority students, witnessing discrimination was not associated with school outcomes, but hearing peers intervene against slurs was associated with increased belongingness. Perceptions of the campus climate were robustly associated with student outcomes, regardless of sexual orientation.